THE ADVERTISEMENT CALL OF THE INDOCHINESE BROWN BULLFROG, Kaloula indochinensis CHAN, BLACKBURN, MURPHY, STUART, EMMETT, HO, AND BROWN, 2013 (ANURA: MICROHYLIDAE) FROM GIA LAI PROVINCE, VIETNAM - Thanh Luan, Nguyen; Thi Tuyet Dung, Tran; Tapley, Benjamin (Journal of Forestry Science and Technology, 2022)
Call descriptions may facilitate studies on behavioural ecology and support taxonomists in their efforts to delimit species. The Indochinese Brown Bullfrog (Kaloula indochinensis) was described in 2013 and occurs in evergreen forest in Indochina. Whilst the tadpole of the species was recently described, little else is known about the biology and ecology of the species including the call characters. In this paper, we describe the male advertisement calls of the Indochinese Brown Bullfrog, Kaloula indochinensis from evergreen forest in Gia Lai province, in the Central Highlands of Vietnam for the first time. This species has a slow and low-pitched call that is similar to the sounds of a trumpet to the human ear. The call description of Kaloula indochinensis is based on recordings from two males. This species has a single call type consisting of a single note per call with a dominant frequency of 0.34 – 0.43 kHz (calls recorded at an air temperature of 20.5°C. The call duration ranged from 194 – 250 milliseconds and the average intercall interval ranged from 481 – 1627 milliseconds. The male advertisement calls of Kaloula indochinensis is compared with the male advertisement calls for the six congeneric species with published male advertisement call descriptions.